If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -3) + 2(14 + -2x) + -2(5x + 2) = -1 Reorder the terms: 3(-3 + 5x) + 2(14 + -2x) + -2(5x + 2) = -1 (-3 * 3 + 5x * 3) + 2(14 + -2x) + -2(5x + 2) = -1 (-9 + 15x) + 2(14 + -2x) + -2(5x + 2) = -1 -9 + 15x + (14 * 2 + -2x * 2) + -2(5x + 2) = -1 -9 + 15x + (28 + -4x) + -2(5x + 2) = -1 Reorder the terms: -9 + 15x + 28 + -4x + -2(2 + 5x) = -1 -9 + 15x + 28 + -4x + (2 * -2 + 5x * -2) = -1 -9 + 15x + 28 + -4x + (-4 + -10x) = -1 Reorder the terms: -9 + 28 + -4 + 15x + -4x + -10x = -1 Combine like terms: -9 + 28 = 19 19 + -4 + 15x + -4x + -10x = -1 Combine like terms: 19 + -4 = 15 15 + 15x + -4x + -10x = -1 Combine like terms: 15x + -4x = 11x 15 + 11x + -10x = -1 Combine like terms: 11x + -10x = 1x 15 + 1x = -1 Solving 15 + 1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 1x = -1 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = -1 + -15 1x = -1 + -15 Combine like terms: -1 + -15 = -16 1x = -16 Divide each side by '1'. x = -16 Simplifying x = -16
| 8-(-3x)=x | | 11=5y+-3y | | -1.1-(-10.1)= | | (6y+8)-(3+5y)=8 | | 400x= | | 15+h=10 | | 3(8)=n(0.08)(300) | | 8x+4=x-14 | | 13x^3-36x=-12x^2 | | 2x-3xm-3x*4=-2m-8 | | 4x-5x-3=0 | | 2x+8y=x-2y | | Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 |